Dynamic Processing 2D Maps Method for Robot’s Trajectory Planning - Shaymaa Azubairi; Alexdener Petunin; Hussam Lefta Alwan; Mohammed Majid Msallam; Amjad J. Humaidi (Proceedings of Engineering and Technology Innovation, 2025)
Unlike common usage of programmed maps, highly robust maps that mimic reality have rarely been tested for path-planning problems with a variety of search algorithms. Meanwhile, utilizing real-like maps might direct studies toward the image processing field and can be time-consuming. Therefore, this study aims to propose a method to effectively and quickly read and process 2D maps in such a way that search algorithms can recognize them. Simulations are conducted on two maps to show the merit of the proposed method. In all simulations, the proposed method successfully read and processed maps in an average time of 1.5043 seconds. Moreover, the search algorithm, which is a probabilistic roadmap can quickly recognize the maps and plan feasible paths from starting points to target points.